Use of Swamp Grass and Agricultural Waste as Materials for Total Mixed Fiber (TMF) in Rations and its Effect on Methane Gas Production and Production Efficiency of Beef Cattle - Imsya, Afnur; Muhakka; Yosi, Fitra (Pakistan Journal of Nutrition, 2016)
The use of total mixed fiber (TMF) in feed production involves mixing of forages from agricultural byproducts that have different fiber fractions, nutritional values and availabilities. The forage materials used in this study were rice straw, palm oil fronds and swamp grass. Here we tested: (1) TMF composition of single samples and (2) TMF of different rations based on the forage materials they contained. The study used in vitro methods and randomized group design to evaluate 5 replicates of 4 different feed rations. The ration compositions were: Ration 1 (R1) = 40% kumpai tembaga swamp grass + 20% rice straw; Ration 2 (R2) = 40% swamp grass + 20% palm oil frond; Ration 3 (R3) = 20% swamp grass + 20% rice straw + 20% palm oil frond; Ration 4 (R4) = 30% rice straw + 30% palm oil frond, which were then added to a standard feed concentrate. In vitro methods were used to measure methane gas production, digestibility of dry matter (DMD), organic matter (OMD) and neutral detergent fiber (NDF, NDFD), as well as NH3-N and partial volatile fatty acid (VFA) concentrations. The results showed that, relative to rations with rice straw and palm oil frond, rations with kumpai tembaga grass produced higher concentrations of acetic, propionic and butyric acid (16.10 mM, 6.05 mM and 5.99, respectively) as well as 9.68 mM methane gas. The optimal TMF composition was 20% swamp grass, 20% rice straw and 20% palm oil frond, which produced 36.32% DMD, 35.96% OMD, 17.86% NDFD and 10.84 mM NH3-N, as well as 12.39 mM acetic acid, 4.39 mM propionic acid, 4.36 mM butyric acid VFAs and 6.91 mM methane gas.